2020
DOI: 10.1039/c9nr10421f
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interactions of cadmium-free quantum dots embedded in a photosensitised polymer surface: efficient killing of multidrug-resistant strains at low ambient light levels

Abstract: Polyurethane incorporated with cadmium-free quantum dots and crystal violet dye kill >99.9% of multi-drug resistant and intrinsically resistant clinical strains of bacteria under ambient light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…To restrict the use of toxic cadmium, Owusu et al 113 developed indium phosphide quantum dots (InP QDs) via a proprietary molecular seeding procedure. The QDs-CV complex was incorporated into PU via the swell-encapsulation-shrink dipping technique, and the obtained PU/QDs-CV film was evaluated for its antibacterial effect on E. coli and P. aeruginosa (Figure 6).…”
Section: Other Metal and Metal Oxide Nanoparticles-incorporated Polyu...mentioning
confidence: 99%
See 1 more Smart Citation
“…To restrict the use of toxic cadmium, Owusu et al 113 developed indium phosphide quantum dots (InP QDs) via a proprietary molecular seeding procedure. The QDs-CV complex was incorporated into PU via the swell-encapsulation-shrink dipping technique, and the obtained PU/QDs-CV film was evaluated for its antibacterial effect on E. coli and P. aeruginosa (Figure 6).…”
Section: Other Metal and Metal Oxide Nanoparticles-incorporated Polyu...mentioning
confidence: 99%
“…The fabricated PU and PU nanocomposites were examined for their antibacterial activity against S. aureus and E. coli bacteria. Even after 24 h of F I G U R E 6 Preparation of antibacterial PU with InP QDs and CV via a non-covalent dipping process 113 [Color figure can be viewed at wileyonlinelibrary.com] incubation, the cell viability was not affected by the presence of pure PU, whereas the GO-and rGO-incorporated PU nanocomposites showed a 100% reduction in cell viability. The graphite-derived PU nanocomposite film displayed 63% inhibition for E. coli and 42% inhibition for S. aureus after 24 h. The antimicrobial action of grapheneincorporated PU nanocomposites may be attributed to the introduction of membrane and oxidation stress (Figure 8).…”
Section: Carbon Materials-based Polyurethane Compositesmentioning
confidence: 99%
“…It is suggested that there are two pathways, known as Type I and Type II mechanisms. As proposed by Owusu and cols [ 94 , 95 ] Type I mechanism involves photo-electron transfer (PET) to generate free radicals such as superoxide anions and hydroxyl radicals. The Type II mechanism involves the formation of reactive singlet oxygen ( 1 O 2 ) from a direct energy transfer from the phtosensitizer to molecular oxygen.…”
Section: Polymeric Materials With Antibacterial Activitymentioning
confidence: 99%
“…Both mechanisms contribute to the formation of ROS that kill bacteria. As the purpose of this study is the use of these complexes in medicine, cadmium free quantum dots were proposed [ 94 ]. The photoactivable mechanism is also proposed in a household solar water disinfection device, where self-supported TiO 2 is placed inside polyethylene terephthalate (PET) bottles to produce clean household water [ 95 ].…”
Section: Polymeric Materials With Antibacterial Activitymentioning
confidence: 99%
“…CV has been chosen for this purpose since it has been reported as a fluorescent marker to study the traverse effect on the Escherichia coli peptidoglycan membrane, as a fluorescent discriminator for the G-quadruplex complex, and so forth. CV-anchored magnetofluorescent nanoparticles were also designed for the detection of bacteria by μ-NMR and optical imaging as point-of-care diagnostics . Cadmium-free quantum dots and CV have been explored as FRET pairs to generate photoactivated reactive oxygen species, and solution-based spectroscopic methods (not image-based assay) were explored to study their antimicrobial activity. , Until now, no effort has been made to explore the image-based FRET assay in bacterial research. In the present investigation, a novel strategy is introduced, wherein an on-site bacterial membrane-reinforced FRET gate was created using an AIE-active polymer gatekeeper (donor) to localize the CV biomarker (acceptor).…”
Section: Introductionmentioning
confidence: 99%